Budget update: relief for lifestyle / Roshidah Safeei and Aniza@Marzita Ishak - Safeei, Roshidah; Marzita Ishak, Aniza (Faculty of Accountancy, UiTM Kedah, 2018)
In budget speech 2017, the government introduced a new lifestyle relief in order to inculcate good reading habits, nurture healthy lifestyles, and enhance usage of computers and internet. It is actually not new lifestyle relief, but comprehensive reliefs which combine a few tax reliefs into one, allowing taxpayers to claim annual assessments. It is a combination of the existing tax relief for reading materials such as books, magazines, journals but excluded newspapers and banned reading materials up to RM1,000 a year for oneself, spouse or child; personal computer up to RM3,000 to be claimable once over a three-year period, and sports equipment for sports activities as defined under the Sports Development Act 1997 up to RM300 a year with a limit of up to RM2,500. Total sum of the reliefs must not exceed RM2,500.